Serially Concatenated Continuous Phase Modulation with SOVA Turbo Decoding - Guo, Zhijie; Cao, Lei (Proceedings of IEEE Southeastcon, 2022)
For a Serially Concatenated Continuous Phase Modulation (SCCPM) system that concatenates a rate of 1/2 Convolutional Code (CC) and an M-ary full response continuous phase modulation (CPM) signal, we design a turbo decoding scheme using the Soft Output Viterbi algorithm (SOVA) and study the system performance. A decomposition model is used in CPM to reduce the number of states and separate the continuous phase encoder (CPE) with the modulator. As a soft-input soft-output (SISO) decoding algorithm, SOVA is used to generate and update the soft information of decoded signal symbols during the iterative process for both the CPM signal and the CC. Newly generated soft information from one component decoder will be used by the other component decoder to constitute an iterative (i.e., turbo) decoding process. Simulation results show that a decoding gain of at least 1 dB can be obtained by using the turbo decoding compared to that without turbo decoding.